Power and Size of Firms as Reflected in Cleaning Subcontractors’ Practices of Social Responsibility - Nisim, Sarit (Journal of business ethics, 2008)
Recent discussions in the area of corporate social responsibility suggest that organizational size has complex meanings and thus requires more scholarly attention. This article explores organizational size in the context of relative power in inter-organizational networks. To shed light on the ways relative power interacts with size we studied social responsibility practices among cleaning subcontractors in three firms of different sizes. Our focus on the network differentiates these firms on the basis of their size and sector. Semi-structured interviews were used to trace cleaning subcontractors’ CSR-related practices. We analyzed subjective reports and discursive practices involved in subcontractors’ self-presentations. While the economic and philanthropic dimensions of social responsibility were presented by the cleaning subcontractors as independent of network constraints, the findings show that the legal and ethical dimensions were subject to large client–firm pressures. What we learn from our data is that the four dimensions of Carroll’s model, the economic, legal, ethical, and philanthropic, should all develop from and be evaluated against a fifth root dimension of inter-personal commitment.